His-bundle pacing to treat an unusual case of chest pain after pacemaker implant. Issue 5 (May 2022) - Parollo, Matteo; Zucchelli, Giulio; Santoro, Mario Giannotti; Barletta, Valentina; Paperini, Luca; Bongiorni, Maria Grazia
Abstract: A 63-year-old man with hypertension and 3-vessel coronary artery disease previously treated with coronary artery bypass graft was admitted to our emergency room complaining of chest pain. He had undergone pacemaker implant 5 months before due to paroxysmal advanced atrioventricular block. Electrocardiography and troponin testing were unremarkable. Echocardiography and chest X-ray ruled out lead displacement and perforation. Interrogation showed normal parameters [right atrium: impedance 550 Ohm bipolar, sensing 2.4 mV bipolar; threshold 0.50 V/0.4 ms bipolar; right ventricle (RV): impedance 580 Ohm bipolar, sensing > 25 mV bipolar; threshold 1.5 V/0.4 ms bipolar and 0.4 V/0.4 ms unipolar]. Pain was evoked only during RV pacing. An electrophysiology study demonstrated painful RV pacing from multiple sites. We hypothesized that pain was associated with pacing-induced dyssynchrony. His-bundle pacing (HBP) was considered as a solution. We achieved HBP with a bipolar fixed-screw catheter connected to a cardiac resynchronization therapy pacemaker generator. During HBP above threshold (4.00 V/1.00 ms) the patient did not complain of any pain. He was discharged 3 days later pain-free with His-bundle lead amplitude set at 5.00 V/1.00 ms. After 6 months the patient was asymptomatic, with the device showing normal functioning. This is the first clinical experience of painful RV pacing treated with HBP. <Learning objective: Painful right ventricular pacing in the absence of perforation is a rare but potentially underdiagnosed condition. Ventricular dyssynchrony could represent the underlying mechanism. Physiological electromechanical activation achieved via His-bundle pacing could represent an effective therapeutic option.>